Novel thermoresponsive particle gels for tissue engineering applications - Cheikh Al Ghanami, Racha (2011)
Biomaterials play an important role in tissue engineering, where they are used as scaffolds for the 3D culture of cells, to help the generation of neo tissues in-vitro and achieve superior tissue engraftment and regeneration in-vivo.